2020
DOI: 10.3991/ijet.v15i05.12277
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Use of Multimedia Technologies in Teaching English Language in Kuwait

Abstract: The way of learning and teaching has been improved and the term of learning is developed. Generally, many researchers try to identify the important factors that affect the usage of multimedia in teaching and learning. However, there are few studies in this area specifically in Kuwait. Therefore, this study comes to fill this gab and identify the factors that influence the usage of multimedia technologies in teaching English language in Kuwait. Consequently, a research model is developed. To evaluate the propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 24 publications
0
13
0
1
Order By: Relevance
“…Al-Ajmi and Aljazzaf, [16] expressed that this article came to recognize the aspects influencing the usage of multimedia technology in English language teaching in Kuwait. To investigate this proposed design, questionnaires and empirical data are gathered.…”
Section: Related Workmentioning
confidence: 99%
“…Al-Ajmi and Aljazzaf, [16] expressed that this article came to recognize the aspects influencing the usage of multimedia technology in English language teaching in Kuwait. To investigate this proposed design, questionnaires and empirical data are gathered.…”
Section: Related Workmentioning
confidence: 99%
“…Three dimensions with seven parameters are used to measure the Critical Success Factor (CFS) of online learning in developing regions. First, the personal dimension with parameters of student characteristics [8,9], internal motivation [21][22][23][24], and instructor/lecturer characteristics [25][26][27]. Second, the system's dimensions with parameters of the quality of institutions and services, infrastructure, and quality of the system, the quality of courses and information [10,12].…”
Section: Introductionmentioning
confidence: 99%
“…In college English teaching, more and more evidence has indicated that traditional teaching approaches can no longer meet the new demand of English teaching [4][5][6]. e brandnew teaching approaches represented by MOOC and others have promoted the development of English teaching to a new height, where the existing English teaching resources can be effectively integrated to improve the teaching efficiency [7].…”
Section: Introductionmentioning
confidence: 99%